2010
DOI: 10.1186/1471-227x-10-16
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delays to admission from the emergency department on inpatient outcomes

Abstract: BackgroundWe sought to determine the impact of delays to admission from the Emergency Department (ED) on inpatient length of stay (LOS), and IP cost.MethodsWe conducted a retrospective analysis of 13,460 adult (≥ 18 yrs) ED visits between April 1 2006 and March 30 2007 at a tertiary care teaching hospital with two ED sites in which the mode of disposition was admission to ICU, surgery or inpatient wards. We defined ED Admission Delay as ED time to decision to admit > 12 hours. The primary outcomes were IP LOS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 10 publications
0
35
0
5
Order By: Relevance
“…Jak wykazały kilkuletnie badania, wydłużony czas oczekiwania pacjentów na przyjęcia w izbie przyjęć podaje połowa szpitali badanych w USA (36). Badania miały na celu analizę kilku metod przyjmowania pacjentów w izbach przyjęć w wybranych szpitalach i szukanie korelacji między każdą z nich w aspekcie utraconych korzyści z powodu oczekiwania pacjentów na przyjęcie.…”
Section: Organizacja Czasu Pracy W Izbie Przyjęćunclassified
See 2 more Smart Citations
“…Jak wykazały kilkuletnie badania, wydłużony czas oczekiwania pacjentów na przyjęcia w izbie przyjęć podaje połowa szpitali badanych w USA (36). Badania miały na celu analizę kilku metod przyjmowania pacjentów w izbach przyjęć w wybranych szpitalach i szukanie korelacji między każdą z nich w aspekcie utraconych korzyści z powodu oczekiwania pacjentów na przyjęcie.…”
Section: Organizacja Czasu Pracy W Izbie Przyjęćunclassified
“…Odnotowano zależność liniową między wydłużają-cym się czasem oczekiwania na przyjęcie i wzrostem tzw. utraconych korzyści (36). Znaczące opóźnienia w przepływie pacjentów w izbie przyjęć mają liczne negatywne konsekwencje, m.in.…”
Section: Organizacja Czasu Pracy W Izbie Przyjęćunclassified
See 1 more Smart Citation
“…6 A study published in 2010 concluded that ED admission delays greater than 12 hours increased inpatient LOS at an annual additional cost of 2.1 million dollars. 7 Owing to limited resources and increasing patient demand, the largest contributing factor to ED crowding is access block 1 -the "diminished access to health care." 8 This multifactorial issue has no single solution, and its resolution will require a systems-approach rather than through the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The figures suggest that There may be a business case for interventions that improve ED flow and reduce admission delay. [4] Another approach to reduce the time delays is using FINC methodology. This methodology is designed mostly for reducing Delay rate in military in C4ISR (Command, Control, Communications, Computers, Intelligence, Surveillance, Reconnaissance) architecture by Dekker.…”
Section: Introductionmentioning
confidence: 99%